(untitled) (Journal of Business Management and Accounting, 2017)
Reforms in the public sector, the world over, has taken a global dimension towards harmonization and convergence of international and national accounting systems for the promotion of useful and standardized financial reporting practices. At the centre of this change is the adoption and application of the international public sector accounting standards (IPSAS) by public sector entities. The cash-basis IPSAS is one of the IPSAS which supports the presentation of the general purpose financial statement (GPFS) for new adopters that intend to migrate to full accrual-based IPSAS. However, despite its essence as a de facto standard mostly adopted by developing countries, limited studies have considered the consideration for its decision-usefulness for financial reporting. The objective of this paper is to propose a conceptual framework that explains the factors of how financial reporting, based on the cash-basis IPSAS, would assist decision usefulness of financial reports to diverse user groups. In addition, the paper identifies potential organizational factors that may strengthen the elaboration of useful financial reporting statement. Based on the literature survey methodology, this paper argues that, identification of usable format that increases understandability of the financial statements for different user groups and an increased support for accounting staff competency, are veritable considerations in the framework for decision useful financial reporting statement in the application of the cash-basis IPSAS.